The regulation of repo markets: Incorporating public interest through a stronger role of civil society - Matthias Thiemann; Marius Birk (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
Regulatory failures, which came to the fore after the financial crisis of 2007-2009, lead to the question of why some activities by financial institutions were not regulated prior to the crisis of 2007, even though regulators knew about certain dangers to financial stability? The repo-market, although centrally involved in the last crisis, still awaits stringent regulation. At the same time, the regulatory cycle seems to come to an end, boding ill for future crises which will be amplified by this market. In this situation, NGOs are needed to make regulators act upon their knowledge and to tighten their regulations.
Keywords: 330; Repo Markets; Shadow Banking; Non-governmental Organizations